2013
DOI: 10.1590/s1516-18462013005000020
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação comportamental do processamento auditivo em indivíduos pós - traumatismo cranioencefálico: estudo piloto

Abstract: OBJETIVO: verificar o desempenho de indivíduos pós-traumatismo cranioencefálico em testes comportamentais para avaliação do processamento auditivo. MÉTODO: participaram da pesquisa 10 indivíduos audiologicamente normais com histórico de trauma craniano. Foram submetidos a: audiometria tonal liminar, logoaudiometria, medidas de imitância acústica (timpanometria e pesquisa dos reflexos acústicos) e avaliação comportamental do processamento auditivo (Testes de Localização Sonora, Memória Sequencial Verbal, Memóri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
4
0
5
Order By: Relevance
“…After ACAT, it could be observed an improvement in the behavioral auditory processing evaluation, with an improvement or even adjustment in auditory abilities (Tables 1 to 4), which are commonly altered in individuals after TBI, as shown in some studies that performed auditory processing evaluation In this population [12][13][14] . The data found in the DCVT Test -Free Recall (Tables 2) demonstrated that the individual presented a greater number of right ear hits in the two moments after ACAT, that is, he showed an right ear advantage that he did not initially demonstrated, which is often associated to left hemispheric dominance for linguistic sounds in right-handed individuals 15 .…”
Section: Discussionmentioning
confidence: 69%
“…After ACAT, it could be observed an improvement in the behavioral auditory processing evaluation, with an improvement or even adjustment in auditory abilities (Tables 1 to 4), which are commonly altered in individuals after TBI, as shown in some studies that performed auditory processing evaluation In this population [12][13][14] . The data found in the DCVT Test -Free Recall (Tables 2) demonstrated that the individual presented a greater number of right ear hits in the two moments after ACAT, that is, he showed an right ear advantage that he did not initially demonstrated, which is often associated to left hemispheric dominance for linguistic sounds in right-handed individuals 15 .…”
Section: Discussionmentioning
confidence: 69%
“…Many individuals who suffer TBI have auditory processing disorder (APD), which can only be identified with special tests (2,3) . Some studies apply the behavioral evaluation of auditory processing in individuals who have suffered TBI and showed changes in this population (4)(5)(6) . Since changes in the auditory pathway that can be found in individuals after TBI and can compromise the communication, it is necessary to propose a rehabilitation program for these patients in order to improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos com adultos que sofreram TCE grave também apresentaram alteração nos processos gnósicos de decodificação, não verbal e organização 12 .…”
Section: Conclusãounclassified
“…Estudos em adultos, que sofreram traumatismo cranioencefálico grave, apresentaram resultados semelhantes 12 .…”
Section: Conclusãounclassified
See 1 more Smart Citation